Analysis of Gene-Environment Interactions Related to Developmental Disorders - Nishimura, Yuhei; Kurosawa, Kenji (Frontiers in Pharmacology, 2022)
Various genetic and environmental factors are associated with developmental disorders (DDs). It has been suggested that interaction between genetic and environmental factors (G×E) is involved in the etiology of DDs. There are two major approaches to analyze the interaction: genome-wide and candidate gene-based approaches. In this mini-review, we demonstrate how these approaches can be applied to reveal the G×E related to DDs focusing on zebrafish and mouse models. We also discuss novel approaches to analyze the G×E associated with DDs.